Assessment of the joint work of battery energy storage systems with power plants on renewable energy sources - Nechaieva T.P. (General Energy Institute of the National Academy of Sciences of Ukraine, 2019)
The rapid development of renewable energy in the world, driven both by the improvement of technologies, the increase in their competitiveness, and the active state support policy aimed at preventing global climate change, led to global transformational shifts in the structure of electricity systems. The increase in the fraction of wind and solar power plants with changeable and intermittent mode of generation causes an increase in the requirements to flexibility of power systems. Energy storage systems can integrate an increased fraction of renewable generation to power systems, because they support the local generation of electricity from variable renewable energy (VRE) in distributive networks and the net infrastructure to balance production from these sources.Battery storage systems, which have extremely fast response times, fast deployment times, and significant scaling, have great prospects for such network services. The article presents a model for estimating the cost efficiency of joint operation of a power plant at VRE, a battery-based energy storage system, and a traditional standby power plant under conditions of ensuring a constant power level of such a system.The results of model calculations of the levelized cost of electricity from a system consisting of a wind power plant, a lithium-ion storage system and a standby thermal power plant showed the economic and environmental benefits of using a standby gas-fired combined-cycle plant as compared to a coal-fired thermal power plant.